Repetitive Sprinting and Running Fatigue in Children with Different Levels of Motor Competence - Dané Coetzee; Wilmarié du Plessis; Bouwien Smits-Engelsman (Children)
Background: Children with motor delays often experience challenges in health-related fitness, but the impact on running skills remains unclear. Previous research has shown that children with motor coordination problems have lower cardiorespiratory fitness, muscle strength, endurance, and higher body weight compared to peers. Few studies have examined anaerobic capacity, muscular power, endurance, running performance, and fatigue in children with developmental coordination disorder (DCD). This study aims to compare repetitive running and running-induced fatigue in typically developing children and those with varying degrees of motor coordination problems. Methods: Groups were classified using the Movement Assessment Battery for Children, second edition (MABC-2), as probably having DCD (p-DCD, ≤5th percentile, age 9.7 (SD 1.6), n = 141), at risk for DCD (r-DCD, 6th–16th percentile, age 9.9 (SD1.6), n = 160), and typically developing (TD, >16th percentile, age 9.6 (SD 1.6), n = 191). Anaerobic fitness and fatigue were assessed using the Children’s Repetitive and Intermittent Sprinting Performance test (CRISP), while lower and upper body muscular strength, running, and agility were measured with the performance and fitness (PERF-FIT) test battery Power and Agility subscale. Age groups (6–9 and 10–12 years) were analyzed to determine when performance deficits emerged. Results: The p-DCD group was significantly slower, had less power, and fatigued more than the r-DCD and TD children (p < 0.01). This was already clearly the case in the 6–9-year-olds, who slowed down already after the first runs, while the older poorly coordinated children started slower than their peers and showed a more gradual decrease in performance over the runs. Conclusions: Moderate coordination differences between r-DCD and TD children did not significantly impact fatigue, but p-DCD children exhibited greater fatigue due to overestimating their start speed, higher body weight, lower power, and reduced agility, especially in younger age groups. (Too) High starting speed, especially in the younger less coordinated children (p-DCD), is likely to lead to more fatigue.